Population Pharmacokinetics of Talazoparib in Patients With Advanced Cancer. (6th September 2019) - Yu, Yanke; Durairaj, Chandrasekar; Shi, Haihong; Wang, Diane D.
Abstract: Poly(ADP‐ribose) polymerase (PARP) inhibitors have been developed to treat cancers associated with somatic BRCA mutations and germline genetic aberrations involved in the DNA damage response. The efficacy, tolerability, and pharmacokinetic/pharmacodynamic (PK/PD) profile of talazoparib, a potent small‐molecule PARP inhibitor, was established in 4 clinical studies in cancer patients (2 phase 1 studies PRP‐001 and PRP‐002, the phase 2 ABRAZO trial, and the phase 3 EMBRACA trial). The current study aimed to describe the population PK of talazoparib and identify covariates that affect talazoparib PK in patients with advanced cancers using pooled data from these 4 studies. Talazoparib PK was well characterized by a 2‐compartment model with first‐order absorption and absorption lag time. Based on covariate analysis, no dose adjustment for talazoparib is required based on a patient's age, sex, baseline body weight, Asian race, the presence of mild renal or hepatic impairment, or use of acid‐reducing agents. A reduced 0.75‐mg daily dose is recommended for patients taking a potent P‐glycoprotein inhibitor and those with moderate renal impairment. Insufficient data were available to establish dosing recommendations for patients with severe renal and moderate or severe hepatic impairment. The PK of a single 1‐mg talazoparib capsule is comparable with 4 0.25‐mg capsules. Talazoparib can be taken with or without food. These data provide support for dosing recommendations and labeling information for talazoparib.